2007
DOI: 10.1063/1.2824873
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted laser ablation of tungsten: Reduction in ablation power threshold due to bursting of holes/bubbles

Abstract: Nanosecond laser ablation of tungsten (W) exposed to helium plasma is investigated using optical emission spectroscopy. Submicrometer-sized holes/bubbles are formed on the surface of W when it was exposed to the helium plasma at a sufficiently high temperature (≳1500–1600K). The emissions from a virgin W (before the helium plasma irradiation) cannot be detected when the fluence is <1J∕cm2; however, the threshold fluence for the detection of neutral W emission after it was exposed to the helium plasma is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Recently, Takamura et al [3] found for the first time that deeply nanostructured tungsten (or ''fuzz'') with an arborescent shape was formed on tungsten-coated graphite via high-flux He plasma irradiation. This structure was demonstrated to greatly change the physical properties of the W surface such as the heat transfer, fuel (deuterium/tritium) retention and erosion rates, which severely impact the operation of fusion devices [4][5][6][7][8]; therefore, it is very important to understand the formation mechanism of fuzz on the surface. To date, various mechanisms have been advocated to explain the formation of such nanostructures experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Takamura et al [3] found for the first time that deeply nanostructured tungsten (or ''fuzz'') with an arborescent shape was formed on tungsten-coated graphite via high-flux He plasma irradiation. This structure was demonstrated to greatly change the physical properties of the W surface such as the heat transfer, fuel (deuterium/tritium) retention and erosion rates, which severely impact the operation of fusion devices [4][5][6][7][8]; therefore, it is very important to understand the formation mechanism of fuzz on the surface. To date, various mechanisms have been advocated to explain the formation of such nanostructures experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have also been applied to the investigation of ablation and melting thresholds on different plasma-exposed W materials, in order to highlight the role of He bubbles on the behavior of W under extreme thermal loads [30,31]. Recently, thermal effects induced on W by ITER-relevant thermal loads have also been mimicked by nanosecond lasers [32].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the heat load on the divertor in previous MCF systems has been unreached parameter. Thus, to predict properties of the divertor under these heat loads, several experiments have been performed using electron [5] or plasma guns [6,7], or intense laser intended to reproduce relevant heat fluxes [8]. These experiments have mainly been employed to evaluate metallurgical characteristics of the tungsten divertor.…”
Section: Introductionmentioning
confidence: 99%